Treatment-Related Adverse Effects in Lung Cancer Patients after Stereotactic Ablative Radiation Therapy. (4th October 2018) - Morias, Stamati; Marcu, Loredana G.; Short, Michala; Giles, Eileen; Potter, Andrew; Shepherd, Justin; Gierlach, Thanh; Bezak, Eva
Abstract : Introduction. Lung cancer is a disease which, despite the advancements in treatment, still has a very poor 5-year survival rate. Stereotactic ablative radiation therapy (SABR) is a highly advanced, sophisticated, and safe treatment which allows patients with early stage lung cancer to be treated effectively without invasive procedures and with excellent clinical outcomes. Avoiding surgery minimises morbidity and recovery time, bettering patients' quality of life. Furthermore, SABR allows patients unsuitable for surgery to still undergo curative treatment. Methods. We aimed to review SABR-related normal tissue toxicities reported in the literature. While many studies assess safety, clinical efficacy, and disease control of SABR for lung cancer, the number of comprehensive reviews that analyse SABR-related side-effects is scarce. This integrative review summarises the toxicities reported in literature based on published clinical trials and tumour location (central or peripheral tumours) for available SABR techniques. Given that the majority of the clinical studies did not report on the statistical significance (e.g., p -values and confidence intervals) of the toxicities experienced by patients, statistical analyses cannot be performed. As a result, adverse events are compiled from clinical reports; however, due to various techniques and nonstandard toxicity reports, no meta-analysis is possible at the current stage of reported data. Results. When comparing lobectomy and SABR in phase III trials, surgery resulted in increased procedure-related morbidity. In phase II trials, very few studies showed high grade toxicities/fatalities as a result of SABR for lung cancer. Gross target volume size was a significant predictor of toxicity. An ipsilateral mean lung dose larger than 9 Gy was significantly associated with radiation pneumonitis. Conclusions. Based on the studies reviewed SABR is a safe treatment technique for lung cancer; however, further well-designed phase III randomised clinical trials are required to produce timely conclusive results and to enable their comparison and statistical analysis.